The Role of Hospital Surfaces and Theatre Environment in Transmission of Nosocomial Infections in a Rural District Hospital in Eastern Uganda - Waako, Christopher Knox; Kateregga, Elvis; Lulenzi, Jalia; Nakhokho, Ephraim; Oloka, Emmanuel; Tebagerwa, Annet; Ibilat, Gorett; Rebecca, Nekaka; Iramiot, Jacob Stanley (Journal of Advances in Medicine and Medical Research, 2018)
Healthcare-associated infections (HAIs) are the "most frequent adverse events" in the delivery of healthcare worldwide. Most of these infections are linked to resistant pathogens harboured by hospital fomites and could persist for a long period of time thereby predisposing patients to HAI. Therefore the aim of this study was to determine the role of hospital surfaces (HS) and theatre environment (TE) in the transmission of drug-resistant pathogens. Materials and Methods: A descriptive cross-sectional study design was employed using a sample of 42 swabs collected from indoor hospital surfaces and settle plate method for the theatre environment. Isolates were cultured under favourable growth conditions and identified using colonal morphology, microscopic appearance on gram stain and biochemical methods. Anti-microbial susceptibility testing was performed using the Kerby-Bour disc diffusion method. Results were analysed using SPSS version 16.0 software package and findings presented in tables, charts and graphs. Results: All plates contained growth either bacterial or fungal (bacteria 66% and fungi 34%), majority isolates included Klebsiella (35%) and aspergillus spp. (26.19%) among bacteria and fungi respectively. Other pathogens isolated included Bacillus, Staphylococcus and Pseudomonas among bacteria and Rodothorula and Cladosporium among fungi. All isolates on settle plates displayed varying numbers of colony forming units ranging from 1.6*102 to 4.2*104 CFU/m3. Enterococcus showed the highest resistance to anti-microbial agents, though the general trend of pathogens tested showed the existence of resistance to the commonly used antibiotics. There was rising resistance to the beta-lactam class of antibiotics whereas vancomycin, linezolid, refampin and cefoxitin showed high susceptibility to the antibiotics. There was a 60% MDR and 2.38% ESBL specifically with pseudomonas. Conclusion and Recommendations: There was a high level of bacterial and fungal colonisation on hospital surfaces and theatre environment with a correspondingly high level of resistance to antimicrobial agents in Ngora Freda Carr Hospital.
Keywords: Bacteria; Fungi; Theatre; Colonization; Anti-microbial resistance; Susceptibility profile